(untitled) (Bangladesh Journal of Medical Science, 2025)
Obstetric complications, particularly postpartum hemorrhage (PPH), are a leading cause of maternal morbidity and mortality worldwide. This retrospective study examines the risk factors associated with hemorrhagic complications in 1,400 patients who delivered between 2019 and 2023. Analyzed variables include age, place of residence, parity, delivery mode, and management methods. The study aims to deepen understanding of these complications to enhance prevention and management strategies. Results indicate that 79% of patients experienced immediate postpartum hemorrhage, while 21% suffered from late-onset hemorrhage. Delivery mode was identified as a crucial factor, with increased risk for instrumental and cesarean deliveries. Additionally, uterine interventions, such as manual removal of placenta and assisted procedures, were associated with elevated hemorrhagic risks. Combination therapies using standardized protocols, including misoprostol and tranexamic acid, demonstrated effectiveness in hemorrhage management. However, disparities based on residence were evident, with rural patients facing limited access to specialized care, potentially exacerbating complications. This study underscores the importance of standardized, proactive management of obstetric complications and advocates for improved healthcare access, particularly in rural areas. Findings provide valuable insights for reducing hemorrhagic risks and improving obstetric outcomes. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 268-278